Endoscopic retrograde pancreatography using single balloon enteroscopy in a patient with smoldering pancreatitis in a distal jejunal pancreas transplant - SEVEN, GÜLSEREN; Seven, GÜLSEREN; Kozarek, Richard A. (My University, 2012)
Portal-enteric drainage of graft secretions is currently the preferred method of pancreatic transplantation and usually created between the donor duodenum and recipient jejunum; however, this anatomy does not allow for easy access to the donor pancreas. We report here the first case of a single balloon assisted-endoscopic retrograde pancreatography in a patient with progressively increasing amylase and lipase in portal-enteric-drained pancreas-kidney transplantation. (c) 2012 Elsevier Masson SAS. All rights reserved.